A heat-resistant high manganese non-magnetic steel
The heat-resistant high-manganese magnetless steel processed through specific composition ratios and processes solves the problems of large eddy current loss and insufficient high-temperature resistance under the alternating magnetic field, and achieves a balance between low magnetic permeability and high-temperature strength, which is suitable for mineral furnace materials.
Patent Information
- Application Number
- CN202410898947.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-05
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-07-05
AI Technical Summary
The existing high-manganese magnetless steel has a large eddy current loss under a strong alternating magnetic field and has insufficient high temperature resistance, resulting in a shortening of the electrical energy loss and service life of the mineral furnace.
The heat-resistant high-manganese magnet-free steel with a specific composition ratio is adopted, including C, Si, Mn, Al, Cr, V, Nb, P, S elements. Through electric furnace/converter smelting, AOD furnace refining, LF refining, continuous casting, heat treatment, rolling and cooling processes, austenite structure is formed, and Al and Cr are added to enhance non-magneticity, V and Nb refine grains, forming VC nanoparticles to improve high temperature performance.
在保证无磁性的前提下,显著提升了钢材的高温强度和抗氧化性能,延长了使用寿命,满足矿热炉的高温服役要求。
Smart Images

Figure CN118854183B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of materials, and in particular to a heat-resistant high-manganese non-magnetic steel. Background Art
[0002] Submerged arc furnace is a typical AC low voltage ultra-high current equipment. The strong alternating magnetic field and eddy current effect generated during operation will cause huge loss of electric energy and damage to ferromagnetic structural parts. Therefore, the materials used in submerged arc furnaces need to have good non-magnetic properties. Secondly, the service temperature of the submerged arc furnace structural parts is above 600℃, and the local radiation high temperature area is greater than 800℃. Long-term high temperature working environment will cause intergranular cracks in stainless steel, and then cause water leakage, which greatly shortens the life of the submerged arc furnace. Therefore, on the basis of non-magnetism, the materials of submerged arc furnaces must also have good high temperature resistance.
[0003] At present, in order to meet the above needs, low magnetic permeability austenitic stainless steel, i.e. weak magnetic permeability steel, is mainly used in the production of submerged arc furnaces in China. However, under a strong alternating magnetic field, the use of this steel can only reduce part of the eddy current loss. If stainless steel is used, it will still cause 5-10% power loss, seriously affecting production costs and causing waste of power.
[0004] For non-magnetic properties, high manganese non-magnetic steel is preferred and has been widely used in transformer housings, etc. At present, there are also many patents disclosing the composition design and smelting methods of high manganese non-magnetic steel, such as: a smelting method of high manganese non-magnetic steel CN202210056013.5, a preparation method of powder metallurgy high manganese non-magnetic steel CN202210281933.7, corrosion-resistant non-magnetic steel and its preparation method CN201910988033.4, Fe-Mn austenitic non-magnetic steel forging method CN201610658 702.8, mainly comparing the rolling process, a new type of high-strength and high-corrosion-resistant non-magnetic stainless steel and its manufacturing method CN201611002016.1, a new type of non-magnetic steel for electromagnetic stirring CN201310657616.1, a non-magnetic steel and its preparation method CN201910147417.3 (essentially heating a certain amount of high manganese steel and copper in stainless steel to achieve improved corrosion resistance, but the improvement in heat resistance is not significant), but these patents focus on the corrosion resistance or strength performance of steel, and their high temperature resistance is poor.
[0005] Therefore, it is urgent to research and develop a new type of steel that is non-magnetic and resistant to high temperatures (high temperature oxidation). Summary of the invention
[0006] The purpose of the present application is to provide a heat-resistant high-manganese non-magnetic steel to solve the above problems.
[0007] To achieve the above objectives, this application adopts the following technical solutions:
[0008] A heat-resistant high manganese non-magnetic steel, calculated by total mass as 100%, comprising:
[0009] C0.17-0.20%, Si0.9-1.2%, Mn21.5-24.5%, Al2.0-2.6%, Cr3.5-4.2%, V0.05-0.1%, Nb0.02-0.1%, P≤0.005%, S≤0.006%, the balance is Fe and unavoidable impurities; the content ratio of Al and Cr is controlled to be 1:(1.8-2.1);
[0010] The preparation method of the heat-resistant high manganese non-magnetic steel comprises:
[0011] The raw materials are sequentially subjected to electric furnace / converter smelting, AOD furnace refining, LF refining, continuous casting, heat treatment, rolling and cooling to obtain the heat-resistant high manganese non-magnetic steel;
[0012] The steel billet obtained by continuous casting is flame cut, and the defects of the steel billet are removed by surface grinding; then the steel billet is sent to a three-stage heating furnace for heat treatment; the initial stage temperature of the heat treatment is 1100-1150°C, the middle stage temperature is 1200-1250°C, the soaking stage temperature is 1100-1150°C, the exit temperature of the heating furnace is 1050-1100°C, and the total heating time does not exceed 90 minutes;
[0013] The starting rolling temperature is 980-1050°C, and the final rolling temperature is 700-730°C;
[0014] The cooling comprises: first cooling to 580-650° C. by air cooling plus water cooling, and then cooling to room temperature by air cooling.
[0015] Preferably, Al particles are used for deep deoxidation after the electric furnace / converter smelting is completed.
[0016] Preferably, when performing the surface grinding, the upper surface is ground off by 3 mm and the lower surface is ground off by 1 mm.
[0017] Preferably, the three-stage heating furnace is heated by natural gas.
[0018] Preferably, the volume percentage of oxygen in the atmosphere of the three-stage heating furnace is controlled within 2%.
[0019] Preferably, water dephosphorization is performed at least once during the rolling process.
[0020] Preferably, the heat-resistant high manganese non-magnetic steel is an austenite structure.
[0021] Preferably, the heat-resistant high manganese non-magnetic steel has a yield strength greater than 500 MPa and a tensile strength greater than 700 MPa at room temperature; and a yield strength greater than 400 MPa and a tensile strength greater than 550 MPa at 600-800°C.
[0022] Preferably, the magnetic permeability of the heat-resistant high manganese non-magnetic steel is less than 1.005 at a magnetic field strength of 200 Oersteds.
[0023] Compared with the prior art, the beneficial effects of this application include:
[0024] The heat-resistant high-manganese non-magnetic steel provided in the present application adds Al and Cr to improve the performance of the steel, and obtains non-magnetic steel resistant to high-temperature oxidation by strictly controlling the content ratio of Al and Cr; adopts V and Nb composite microalloying means, and adopts Nb element to refine the grains, which significantly improves the mechanical properties at room temperature and high temperature. By using the V element, a large amount of VC nanoparticles are precipitated under the conditions of 600-800℃, which plays a significant precipitation strengthening role on the steel, especially under the service conditions of 600-800℃ of the steel, a large amount of VC particles are precipitated through high-temperature creep, which significantly improves the high-temperature performance of the steel. On the whole, through the composition design and the reasonable controlled rolling and controlled cooling system, the role of the alloying elements is brought into play, and the high-temperature strength and high-temperature oxidation resistance of the steel are achieved under the condition of ensuring the low magnetic permeability of the non-magnetic steel.
[0025] The heat-resistant high manganese non-magnetic steel provided in this application has a yield strength greater than 500MPa and a tensile strength greater than 700MPa at room temperature. The yield strength is greater than 400MPa and the tensile strength is greater than 550MPa at 600-800℃. After 5 days of high-temperature creep, the yield strength increases by more than 5%, and the tensile strength increases by more than 10%. At a service temperature of 600-800℃, a composite dense oxide layer is formed on the surface of the steel, the outermost layer is a Mn oxide layer, the middle layer is a Cr oxide layer, and the oxide layer and the collective are dense aluminum oxide layers. The multi-layer composite structure effectively hinders the mass transfer of oxygen, thereby effectively resisting high-temperature oxidation. The high-temperature oxidation resistance is similar to that of S304 stainless steel, which fully meets the requirements of materials for submerged arc furnaces. According to the national standard GB / T 13303-1991, the steel meets the full oxidation resistance standard and has a long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0027] Figure 1 This is an electron microscope photo of the oxide layer morphology of Example 1;
[0028] Figure 2 This is the EDS surface scan analysis result of the oxide layer in Example 3;
[0029] Figure 3 This is an electron microscope photo of the oxide layer morphology of Example 3;
[0030] Figure 4 This is the EDS surface scan analysis result of the oxide layer of Comparative Example 1;
[0031] Figure 5 This is an electron microscope photo of the oxide layer morphology of Comparative Example 1;
[0032] Figure 6 This is the EDS surface scan analysis result of the oxide layer of Comparative Example 2;
[0033] Figure 7 This is an electron microscope photo of the oxide layer morphology of Comparative Example 2;
[0034] Figure 8 This is the EDS surface scan analysis result of the oxide layer of Comparative Example 3;
[0035] Fig. 9 This is an electron microscope photo of the oxide layer morphology of Comparative Example 3;
[0036] Fig.10 This is the EDS surface scan analysis result of the oxide layer of Comparative Example 4;
[0037] Fig.11 This is an electron microscope photo of the oxide layer morphology of Comparative Example 4;
[0038] Fig.12 This is the EDS surface scan analysis result of the oxide layer of Comparative Example 5;
[0039] Fig.13 This is an electron microscope photo of the oxide layer morphology of Comparative Example 5;
[0040] Fig.14 This is the EDS surface scan analysis result of the oxide layer of Comparative Example 6;
[0041] Fig.15 This is an electron microscope photograph of the oxide layer morphology of comparative example 6. DETAILED DESCRIPTION
[0042] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:
[0043] A heat-resistant high manganese non-magnetic steel, calculated by total mass as 100%, comprising:
[0044] C0.17-0.20%, Si0.9-1.2%, Mn21.5-24.5%, Al2.0-2.6%, Cr3.5-4.2%, V0.05-0.1%, Nb0.02-0.1%, P≤0.005%, S≤0.006%, the balance is Fe and unavoidable impurities; the content ratio of Al and Cr is controlled to be 1:(1.8-2.1);
[0045] C is an austenite-forming element. The main function of carbon in steel is to increase the strength of steel and balance the austenite structure. As the carbon content in steel increases, the strength of steel increases accordingly. However, excessive carbon content will reduce the plasticity, toughness and oxidation resistance of steel, while promoting aging brittleness and deteriorating weldability. Therefore, the C content in the smelting process should not be too high. AOD is used for decarburization in this application.
[0046] Mn is the main element for stabilizing austenite. It can refine the structure of steel and thus improve the strength of the material, but it will reduce the oxidation resistance of steel. The amount of Mn added should not be too much.
[0047] Al is the main antioxidant element. When added to steel, it can form an oxide film on the surface of the steel, which hinders the further oxidation of the steel and thus improves the steel's antioxidant capacity.
[0048] When the content of Cr in steel is low, it can stabilize austenite and form stable carbides with C, which can refine grains and strengthen precipitation, and also have an anti-oxidation effect. The addition of Cr will thicken the alumina film and significantly improve the high temperature oxidation resistance of steel.
[0049] Si, like chromium, can form a dense FeO·SiO2 oxide layer in steel, that is, a passivating oxide film, which improves the steel's resistance to high-temperature oxidation and can partially replace Cr.
[0050] The addition of microalloying elements Nb and V mainly forms carbonitrides, which play a role in grain refinement and precipitation strengthening. In addition, the precipitation temperature of V carbides is relatively low, which can cause high-temperature creep in steel and improve the high-temperature performance of steel.
[0051] Although adding high Cr alone can improve high temperature oxidation resistance, it increases cost and affects non-magnetism. Adding high Al alone can also improve high temperature oxidation resistance, but it brings huge challenges to continuous casting. The appropriate content will not only not affect the production of existing high manganese non-magnetic steel, but also will not significantly increase costs. Therefore, the present application improves the oxidation resistance of steel by adding Al and Cr at the same time while ensuring a high Si content.
[0052] Optionally, in the heat-resistant high manganese non-magnetic steel, the C content can be 0.17%, 0.18%, 0.19%, 0.20% or any value between 0.17-0.20%, the Si content can be 0.9%, 1.0%, 1.1%, 1.2% or any value between 0.9-1.2%, and the Mn content can be 21.5%, 22.0%, 22.5%, 23.0%, 23.5%, 24.0%, 24.5%. or any value between 21.5-24.5%, the Al content may be 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6% or any value between 2.0-2.6%, the Cr content may be 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2% or any value between 3.5-4.2%, the V content may be 0.05%, The content of Nb can be 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1% or any value between 0.05-0.1%, the content of P can be 0.001%, 0.002%, 0.003%, 0.0 0.04%, 0.005% or any value ≤0.005%, the S content can be 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006% or any value ≤0.006%, and the balance is Fe and unavoidable impurities; the content ratio of Al to Cr can be 1:1.8, 1:1.9, 1:2.0, 1:2.1 or any value between 1:(1.8-2.1);
[0053] The preparation method of the heat-resistant high manganese non-magnetic steel comprises:
[0054] The raw materials are sequentially subjected to electric furnace / converter smelting, AOD furnace refining, LF refining, continuous casting, heat treatment, rolling and cooling to obtain the heat-resistant high manganese non-magnetic steel;
[0055] The steel billet obtained by continuous casting is flame cut, and the defects of the steel billet are removed by surface grinding; then the steel billet is sent to a three-stage heating furnace for heat treatment; the initial stage temperature of the heat treatment is 1100-1150°C, the middle stage temperature is 1200-1250°C, the soaking stage temperature is 1100-1150°C, the exit temperature of the heating furnace is 1050-1100°C, and the total heating time does not exceed 90 minutes;
[0056] Optionally, the initial stage temperature of the heat treatment may be 1100°C, 1110°C, 1120°C, 1130°C, 1140°C, 1150°C or any value between 1100-1150°C, the middle stage temperature may be 1200°C, 1210°C, 1220°C, 1230°C, 1240°C, 1250°C or any value between 1200-1250°C, and the soaking stage temperature may be 1100°C, 1110°C, 1120°C, 1130°C, 1140°C, 1150°C or any value between 1100-1150°C. 30°C, 1140°C, 1150°C or any value between 1100-1150°C, the temperature out of the heating furnace can be 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C or any value between 1050-1100°C, and the total heating time can be 30min, 40min, 50min, 60min, 70min, 80min, 90min or any value not exceeding 90min;
[0057] The starting rolling temperature is 980-1050°C, and the final rolling temperature is 700-730°C;
[0058] Optionally, the starting rolling temperature may be 980°C, 990°C, 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C or any value between 980-1050°C, and the final rolling temperature may be 700°C, 710°C, 720°C, 730°C or any value between 700-730°C;
[0059] The cooling comprises: first cooling to 580-650° C. by air cooling plus water cooling, and then cooling to room temperature by air cooling.
[0060] Optionally, the terminal temperature of the cooling by air cooling plus water cooling can be 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C or any value between 580-650°C.
[0061] The Ni element can increase the strength of steel while maintaining good plasticity and toughness, and can improve the oxidation resistance of steel. However, nickel resources are scarce and the cost is high. Therefore, the development of Ni-saving or Ni-free steel is the development trend of the steel industry, which is of great significance to the cost reduction of related steel grades. Therefore, this application adopts relatively cheap Al and Cr elements to add, significantly improve the oxidation resistance of steel, and by adding a small amount of microalloying elements Nb and V, improve the room temperature and high temperature mechanical properties of steel, so as to replace Ni and achieve low cost of steel.
[0062] It should be noted that in the process, decarburization is carried out in an AOD furnace, and ferrovanadium and ferroniobium are added for alloying, and electrolytic Mn is added during LF refining for Mn alloying.
[0063] The appropriate microalloying process can significantly enhance the room temperature and high temperature mechanical properties of steel. The corresponding controlled cooling process parameters are also key. The appropriate controlled cooling process can effectively transform the hardened austenite into a recrystallized phase for refinement. Through a small amount of reasonable alloying mechanism, the oxidation resistance of steel is significantly improved, the carbon emissions generated by the preparation of alloy elements are reduced, and the overall carbon emissions of heat-resistant high manganese non-magnetic steel production are further reduced.
[0064] In an optional embodiment, Al particles are used for deep deoxidation after the electric furnace / converter smelting is completed.
[0065] In an optional embodiment, when performing the surface grinding, the upper surface is ground off by 3 mm and the lower surface is ground off by 1 mm.
[0066] In an optional embodiment, the three-stage heating furnace is heated by natural gas.
[0067] In an optional embodiment, the volume percentage of oxygen in the atmosphere of the three-stage heating furnace is controlled within 2%.
[0068] In an optional embodiment, water dephosphorization is performed at least once during the rolling process.
[0069] In an optional embodiment, the heat-resistant high manganese non-magnetic steel is an austenite structure.
[0070] In an optional embodiment, the heat-resistant high manganese non-magnetic steel has a yield strength greater than 500 MPa and a tensile strength greater than 700 MPa at room temperature; and a yield strength greater than 400 MPa and a tensile strength greater than 550 MPa at 600-800°C.
[0071] In an optional embodiment, the magnetic permeability of the heat-resistant high manganese non-magnetic steel is less than 1.005 at a magnetic field strength of 200 Oersteds.
[0072] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0073] Example 1
[0074] This embodiment provides a heat-resistant high manganese non-magnetic steel, the composition of which is shown in Table 1 below:
[0075] Table 1 Composition of heat-resistant high manganese non-magnetic steel provided in Example 1 (wt%)
[0076] C Si Mn Al Cr V Nb P S 0.18 0.9 22.5 2.3 4.1 0.08 0.05 0.003 0.004
[0077] The preparation method is as follows:
[0078] This type of steel is produced using the converter-AOD furnace-LF refining-continuous casting-rolling process.
[0079] The converter smelting temperature is 1450-1662℃, the tapping temperature is 1640-1660℃, the AOD smelting temperature is 1580-1625℃, the tapping temperature is 1610-1630℃, the LF refining temperature is 1560-1600℃, the tapping temperature is 1590-1610℃, and the tundish temperature range is 1450-1480℃.
[0080] The converter is dephosphorized and then enters the AOD furnace for decarburization. In the reduction stage, the slag basicity is controlled to 2.2-3.0, aluminum particles are added for deoxidation, and ferroniobium and ferrovanadium are added for vanadium alloying; LF refining is then carried out, and Mn alloying is carried out; finally, the continuous casting process is entered, the middle package temperature is 1440-1480℃, the casting speed is 0.7-1.0m / min, and the ingot is obtained. The ingot is cut by flame cutting, and the defects of the ingot are removed by surface grinding. The upper surface is ground off by 3mm and the lower surface is ground off by 1mm. The ingot enters the three-stage heating furnace for heating. The heating furnace is heated by natural gas, and the volume proportion of atmospheric oxygen is controlled to be less than 2%. The temperature of the initial section is controlled at 1150℃, the temperature of the middle section is controlled at 1200℃, the temperature of the soaking section is controlled at 1100℃, the temperature of the ingot out of the heating furnace is controlled at 1050℃, and the total heating time is 90min (30min each, the same below). The starting temperature is controlled at 1020℃, and the final temperature is controlled at 700℃. During the rolling process, water dephosphorization is carried out once. Air cooling and water cooling are used for forced cooling, and the final cooling temperature is controlled at 600℃, followed by air cooling.
[0081] After testing, the steel is austenitic and has a magnetic permeability of 1.003 at 200 Oersted magnetic field. The yield strength is 535MPa at room temperature and the tensile strength is 740MPa. The initial yield strength is 480MPa and the tensile strength is 590MPa at 600-800℃. After 5 days of high temperature creep, the yield strength is increased to 540MPa and the tensile strength is 670MPa.
[0082] The steel was tested according to the national standard GB / T 13303-1991. The steel was calcined at 600℃ in air atmosphere for 1000h. The oxidation rate of the steel was 0.05g / m 2 ·h, reaching the standard of complete antioxidant performance, with good antioxidant performance.
[0083] Figure 1 This is an electron microscope photograph of the oxide layer morphology of Example 1.
[0084] Example 2
[0085] This embodiment provides a heat-resistant high manganese non-magnetic steel, the composition of which is shown in Table 2 below:
[0086] Table 2 Composition of heat-resistant high manganese non-magnetic steel provided in Example 2 (wt%)
[0087] C Si Mn Al Cr V Nb P S 0.20 1.1 23.5 2.0 3.6 0.06 0.03 0.002 0.003
[0088] The preparation method is as follows:
[0089] This type of steel is produced by the process of electric furnace-AOD furnace-LF refining-continuous casting-rolling. Dephosphorization is carried out in the electric furnace, and the production process after the electric furnace is the same as that in Example 1. The ingot enters a three-stage heating furnace for heating. The heating furnace is heated by natural gas, and the volume proportion of atmospheric oxygen is controlled to be less than 2%. The initial stage temperature is controlled at 1130°C, the middle stage temperature is controlled at 1250°C, the equalizing stage temperature is controlled at 1150°C, the billet temperature out of the heating furnace is controlled at 1080°C, and the total heating time is 90min. The starting temperature is controlled at 1050°C, and the final temperature is controlled at 730°C. Water dephosphorization is performed once during the rolling process. Forced cooling is performed by air cooling and water cooling, and the final cooling temperature is controlled at 640°C, followed by air cooling.
[0090] After testing, the steel is austenitic and has a magnetic permeability of 1.002 at 200 oersted magnetic field strength. The yield strength is 520MPa at room temperature and the tensile strength is 710MPa. The initial yield strength is 443MPa and the tensile strength is 562MPa at 600-800℃. After 5 days of high temperature creep, the yield strength is increased to 470MPa and the tensile strength is 610MPa.
[0091] The steel was tested according to the national standard GB / T 13303-1991. The steel was calcined at 600℃ in air atmosphere for 1000h. The oxidation rate of the steel was 0.08g / m 2 ·h, reaching the standard of complete antioxidant performance, with good antioxidant performance.
[0092] Example 3
[0093] This embodiment provides a heat-resistant high manganese non-magnetic steel, the composition of which is shown in Table 3 below:
[0094] Table 3 Composition of heat-resistant high manganese non-magnetic steel provided in Example 3 (wt%)
[0095] C Si Mn Al Cr V Nb P S 0.18 1.0 24.5 2.5 4.2 0.1 0.1 0.002 0.003
[0096] The preparation method is as follows:
[0097] This type of steel is produced by converter-AOD furnace-LF refining-continuous casting-rolling process. The production process is the same as that in Example 1. The ingot is heated in a three-stage heating furnace. The heating furnace is heated by natural gas, and the volume proportion of atmospheric oxygen is controlled to be less than 2%. The initial temperature is controlled at 1150°C, the middle temperature is controlled at 1250°C, the soaking temperature is controlled at 1150°C, the billet temperature out of the heating furnace is controlled at 1100°C, and the total heating time is 90min. The starting temperature is controlled at 1050°C, and the final temperature is controlled at 730°C. Water dephosphorization is performed once during the rolling process. Forced cooling is performed by air cooling and water cooling, and the final cooling temperature is controlled at 650°C, followed by air cooling.
[0098] After testing, the steel is austenitic and has a magnetic permeability of 1.002 at 200 oersted magnetic field strength. The yield strength is 580MPa at room temperature and the tensile strength is 790MPa. The initial yield strength is 513MPa and the tensile strength is 605MPa at 600-800℃. After 5 days of high temperature creep, the yield strength is increased to 565MPa and the tensile strength is 682MPa.
[0099] The steel was tested according to the national standard GB / T 13303-1991. The steel was calcined at 600℃ in air atmosphere for 1000h. The oxidation rate of the steel was 0.04g / m 2 ·h, reaching the standard of complete antioxidant performance, with good antioxidant performance.
[0100] The EDS surface scan analysis results of the oxide layer are as follows: Figure 2 The electron microscope photo of the oxide layer morphology is shown in Figure 3 shown.
[0101] Comparative Example 1
[0102] This comparative example provides a non-magnetic steel, the composition of which is shown in Table 4 below:
[0103] Table 4 Composition of non-magnetic steel provided in Comparative Example 1 (wt%)
[0104] C Si Mn V Nb P S 0.18 1.0 24.5 0.1 0.1 0.002 0.004
[0105] The steel production method is exactly the same as that in Example 3, except that compared with Example 3, no Al and Cr elements are added to this steel.
[0106] After testing, the steel is austenitic and has a magnetic permeability of 1.005 at 200 oersted magnetic field strength. The yield strength is 560MPa at room temperature and the tensile strength is 710MPa. The initial yield strength is 492MPa and the tensile strength is 593MPa at 600-800℃. After 5 days of high-temperature creep, the yield strength is increased to 540MPa and the tensile strength is 660MPa. Compared with the samples with added Al and Cr, the mechanical properties are slightly reduced, but not obvious.
[0107] The steel was tested according to the national standard GB / T 13303-1991. The steel was calcined at 600℃ in air atmosphere for 1000h, and then EDS surface scanning was performed to observe the morphology of the steel oxide layer and the oxide layer at the steel base. The EDS surface scanning did not find an obvious dense oxide layer, and obvious oxygen channels appeared. The SEM image of the oxide layer also showed that there were many obvious holes in the oxide layer, the mass transfer of oxygen was enhanced, and the oxidation resistance was reduced. Finally, the oxidation rate of the steel was 30g / m 2 h, non-oxidation resistant steel.
[0108] The EDS surface scan analysis results of the oxide layer are as follows: Figure 4 The electron microscope photo of the oxide layer morphology is shown in Figure 5 As shown (morphology at different positions and different magnified sizes).
[0109] Comparative Example 2
[0110] This comparative example provides a non-magnetic steel, the composition of which is shown in Table 5 below:
[0111] Table 5 Composition of non-magnetic steel provided in Comparative Example 2 (wt%)
[0112] C Si Mn Al V Nb P S 0.18 1.0 24.5 2.5 0.1 0.1 0.003 0.002
[0113] The steel production method is exactly the same as that in Example 3, except that compared with Example 3, no Cr element is added to this steel.
[0114] After testing, the steel is austenitic and has a magnetic permeability of 1.005 at 200 oersted magnetic field strength. The yield strength is 565MPa at room temperature and the tensile strength is 712MPa. The initial yield strength is 490MPa and the tensile strength is 590MPa at 600-800℃. After 5 days of high-temperature creep, the yield strength is increased to 539MPa and the tensile strength is 661MPa. Compared with the samples with added Al and Cr, the mechanical properties have not changed much.
[0115] The steel was tested according to the national standard GB / T 13303-1991. The steel was calcined at 600℃ in air atmosphere for 1000h, and then EDS surface scanning was performed to observe the morphology of the steel oxide layer and the oxide layer at the steel base. The EDS surface scanning image found that the Al oxide layer was thinner, and the SEM image of the oxide layer also showed that there were many obvious holes in the oxide layer, the mass transfer of oxygen was enhanced, and the oxidation resistance was reduced. Finally, the oxidation rate of the steel was 5g / m 2 ·h, weak antioxidant property.
[0116] The EDS surface scan analysis results of the oxide layer are as follows: Figure 6 The electron microscope photo of the oxide layer morphology is shown in Figure 7 shown.
[0117] Comparative Example 3
[0118] This comparative example provides a non-magnetic steel, the composition of which is shown in Table 6 below:
[0119] Table 6 Composition of non-magnetic steel provided in Comparative Example 3 (wt%)
[0120] C Si Mn Cr V Nb P S 0.18 1.0 24.5 4.2 0.1 0.1 ≤0.005 ≤0.006
[0121] The steel production method is exactly the same as that in Example 3, except that compared with Example 3, no Al element is added to this steel.
[0122] After testing, the steel is austenitic and has a magnetic permeability of 1.002 at 200 oersted magnetic field strength. The yield strength is 547MPa at room temperature and the tensile strength is 721MPa. The initial yield strength is 489MPa and the tensile strength is 598MPa at 600-800℃. After 5 days of high-temperature creep, the yield strength is increased to 541MPa and the tensile strength is 667MPa. Compared with the samples with added Al and Cr, the mechanical properties have not changed much.
[0123] The steel was tested according to the national standard GB / T 13303-1991. The steel was calcined at 600℃ in air atmosphere for 1000h, and then EDS surface scanning was performed to observe the morphology of the steel oxide layer and the oxide layer at the steel base. The EDS surface scanning image found the presence of Cr oxide layer, but the oxide layer was not dense. The SEM image of the oxide layer also showed that there were many obvious holes in the oxide layer, the mass transfer of oxygen was enhanced, and the oxidation resistance was reduced. Finally, the oxidation rate of the steel was 4.6g / m 2 ·h, weak antioxidant property.
[0124] The EDS surface scan analysis results of the oxide layer are as follows: Figure 8 The electron microscope photo of the oxide layer morphology is shown in Fig. 9 shown.
[0125] Comparative Example 4
[0126] This comparative example provides a non-magnetic steel, the composition of which is shown in Table 7 below:
[0127] Table 7 Composition of non-magnetic steel provided in Comparative Example 4 (wt%)
[0128] C Si Mn Al Cr V Nb P S 0.18 1.0 24.5 5.2 2.0 0.1 0.1 0.002 0.004
[0129] The steel production method is exactly the same as that in Example 3, except that the amount of Cr added to this steel is relatively lower than that in Example 3.
[0130] After testing, the steel is austenitic and has a magnetic permeability of 1.003 at 200 oersted magnetic field strength. The yield strength is 556MPa at room temperature and the tensile strength is 739MPa. The initial yield strength at 600-800°C is 494MPa and the tensile strength is 607MPa. After 5 days of high-temperature creep, the yield strength is increased to 579MPa and the tensile strength is 685MPa. Compared with the samples designed in this application with the addition of Al and Cr, the mechanical properties have not changed much.
[0131] The steel was tested according to the national standard GB / T 13303-1991. The steel was calcined at 600℃ in air atmosphere for 1000h, and then EDS surface scanning was performed to observe the morphology of the steel oxide layer and the oxide layer at the steel base. The EDS surface scanning image showed the presence of Al and Cr oxide layers, but the oxide layers were not dense. The SEM image of the oxide layer also showed that some holes appeared in the oxide layer. Finally, the oxidation rate of the steel was 0.8g / m 2 h, which is an oxidation-resistant steel, but its oxidation resistance is still weaker than that of the steel designed in this application.
[0132] The EDS surface scan analysis results of the oxide layer are as follows: Fig.10 The electron microscope photo of the oxide layer morphology is shown in Fig.11 shown.
[0133] Comparative Example 5
[0134] This comparative example provides a non-magnetic steel, the composition of which is shown in Table 8 below:
[0135] Table 8 Composition of non-magnetic steel provided in Comparative Example 5 (wt%)
[0136] C Si Mn Al Cr V Nb P S 0.18 1.0 24.5 1.6 4.2 0.1 0.1 0.003 0.005
[0137] The steel production method is exactly the same as that in Example 3, except that the amount of Al added to this steel is relatively lower than that in Example 3.
[0138] After testing, the steel is austenitic and has a magnetic permeability of 1.003 at 200 oersted magnetic field strength. The yield strength is 548MPa at room temperature and the tensile strength is 729MPa. The initial yield strength at 600-800°C is 490MPa and the tensile strength is 596MPa. After 5 days of high-temperature creep, the yield strength is increased to 571MPa and the tensile strength is 679MPa. Compared with the samples designed in this application with the addition of Al and Cr, the mechanical properties have not changed much.
[0139] The steel was tested according to the national standard GB / T 13303-1991. The steel was calcined at 600℃ in air atmosphere for 1000h, and then EDS surface scanning was performed to observe the morphology of the steel oxide layer and the oxide layer at the steel base. The EDS surface scanning image showed the presence of Al and Cr oxide layers, but the aluminum oxide layer was thin. The SEM image of the oxide layer also showed that some holes appeared in the oxide layer. Finally, the oxidation rate of the steel was 1.2g / m 2 h, is a secondary oxidation resistant steel, and its oxidation resistance is still weaker than the steel designed in this application.
[0140] The EDS surface scan analysis results of the oxide layer are as follows: Fig.12 The electron microscope photo of the oxide layer morphology is shown in Fig.13 shown.
[0141] Comparative Example 6
[0142] This comparative example provides a non-magnetic steel, the composition of which is shown in Table 9 below:
[0143] Table 9 Composition of non-magnetic steel provided in Comparative Example 6 (wt%)
[0144] C Si Mn Al Cr V Nb P S 0.18 1.0 24.5 1.6 1.5 0.1 0.1 0.003 0.003
[0145] The steel production method is exactly the same as that in Example 3, except that compared with Example 3, the addition amounts of Al and Cr in this steel are lower.
[0146] After testing, the steel is austenitic and has a magnetic permeability of 1.003 at 200 oersted magnetic field strength. The yield strength at room temperature is 545MPa and the tensile strength is 719MPa. The initial yield strength at 600-800°C is 486MPa and the tensile strength is 590MPa. After 5 days of high-temperature creep, the yield strength is increased to 568MPa and the tensile strength is 670MPa. Compared with the samples designed in this application with the addition of Al and Cr, the mechanical properties have not changed much.
[0147] The steel was tested according to the national standard GB / T 13303-1991. The steel was calcined at 600℃ in air atmosphere for 1000h, and then EDS surface scanning was performed to observe the morphology of the steel oxide layer and the oxide layer at the steel base. The EDS surface scanning image showed the presence of Al and Cr oxide layers, but the oxide layers were not dense, especially the Al oxide layer. The SEM image of the oxide layer also showed that some holes appeared in the oxide layer. Finally, the oxidation rate of the steel was 2.3g / m 2 h, is a secondary oxidation resistant steel, and its oxidation resistance is still weaker than the steel designed in this application.
[0148] The EDS surface scan analysis results of the oxide layer are as follows: Fig.14 The electron microscope photo of the oxide layer morphology is shown in Fig.15 shown.
[0149] Comparative Example 7
[0150] This comparative example provides a non-magnetic steel, and the composition of the designed non-magnetic steel is different from that of Example 3 in that V and Nb microalloying elements are not added. The production process and key process parameters are exactly the same as those of Example 3.
[0151] After testing, the steel is austenitic and has a magnetic permeability of 1.003 at 200 oersted magnetic field strength. The yield strength is 397MPa at room temperature and the tensile strength is 665MPa. The yield strength is 367MPa and the tensile strength is 561MPa at the initial stage at 600-800℃. The strength will not increase during subsequent use.
[0152] The steel was tested according to the national standard GB / T 13303-1991. The steel was calcined at 600℃ in air atmosphere for 1000h. The oxidation rate of the steel was 0.041g / m 2 h, reaching the standard of complete oxidation resistance, with good oxidation resistance. Therefore, not adding V and Nb alloy elements will have little effect on the oxidation resistance of steel itself, but will seriously deteriorate the room temperature and high temperature mechanical properties of steel, making it unable to meet high temperature use.
[0153] Comparative Example 8
[0154] This comparative example provides a non-magnetic steel, the composition of which is shown in Table 10 below:
[0155] Table 10 Composition of non-magnetic steel provided in Comparative Example 8 (wt%)
[0156] C Si Mn Al Cr V P S 0.18 1.0 24.5 2.5 4.2 0.1 0.002 0.004
[0157] This comparative example provides a non-magnetic steel. The designed non-magnetic steel smelting method is the same as that of Example 3, but no Nb microalloying element is added.
[0158] After testing, the steel is austenitic and has a magnetic permeability of 1.002 at 200 oersted magnetic field strength. The yield strength at room temperature is 542MPa and the tensile strength is 763MPa. The initial yield strength at 600-800°C is 496MPa and the tensile strength is 597MPa. After 5 days of high temperature creep, the yield strength is increased to 512MPa and the tensile strength is 650MPa. All properties are reduced compared to Example 3.
[0159] The steel was tested according to the national standard GB / T 13303-1991. The steel was calcined at 600℃ in air atmosphere for 1000h. The oxidation rate of the steel was 0.041g / m 2 h, reaching the standard of complete oxidation resistance, and having good oxidation resistance. Therefore, not adding Nb alloy elements has little effect on the oxidation resistance of steel itself.
[0160] Comparative Example 9
[0161] This comparative example provides a non-magnetic steel, the composition of which is shown in Table 11 below:
[0162] Table 11 Composition of non-magnetic steel provided in Comparative Example 9 (wt%)
[0163] C Si Mn Al Cr Nb P S 0.18 1.0 24.5 2.5 4.2 0.1 0.002 0.004
[0164] This comparative example provides a non-magnetic steel. The designed non-magnetic steel smelting method is the same as that of Example 3, but no V micro-alloying element is added.
[0165] After testing, the steel is austenitic, and the magnetic permeability is 1.002 at 200 oersted magnetic field strength. The yield strength is 576MPa at room temperature and the tensile strength is 768MPa. The initial yield strength at 600-800°C is 498MPa and the tensile strength is 592MPa. After 5 days of high-temperature creep, the yield strength is increased to 479MPa and the tensile strength is 586MPa. All properties are reduced compared to Example 3, and after 5 days of high-temperature service, the performance will be reduced due to oxidation of the material.
[0166] The steel was tested according to the national standard GB / T 13303-1991. The steel was calcined at 600℃ in air atmosphere for 1000h. The oxidation rate of the steel was 0.041g / m 2 h, reaching the standard of complete oxidation resistance, and having good oxidation resistance. Therefore, not adding V alloy elements has little effect on the oxidation resistance of steel itself.
[0167] Comparative Example 10
[0168] This comparative example provides a non-magnetic steel having the same composition as that of Example 3.
[0169] The steel smelting process is exactly the same as that in Example 3. The ingot is heated in a three-stage heating furnace. The heating furnace is heated by natural gas, and the volume proportion of atmospheric oxygen is controlled to be less than 2%. The initial temperature is controlled at 1150°C, the middle temperature is controlled at 1250°C, the soaking temperature is controlled at 1150°C, the billet temperature out of the heating furnace is controlled at 1100°C, and the total heating time is 90min. The opening temperature is controlled at 1050°C, and the final temperature is controlled at 730°C. Water dephosphorization is performed once during the rolling process. The final cooling temperature is controlled at 680°C, followed by air cooling.
[0170] After testing, the steel has an austenite structure and a magnetic permeability of 1.002 at a magnetic field strength of 200 oersteds. The yield strength at room temperature is 560MPa and the tensile strength is 765MPa. The initial yield strength at 600-800°C is 492MPa and the tensile strength is 581MPa. After 5 days of high-temperature creep, the yield strength is increased to 491MPa and the tensile strength is 583MPa. Compared with Example 3, the final cooling temperature is controlled at 680°C, which is higher than the set temperature of this application. The VC precipitation time is long and the particles are coarse, which contributes little to the room temperature performance and is not conducive to the subsequent improvement of high temperature performance.
[0171] The steel was tested according to the national standard GB / T 13303-1991. The steel was calcined at 600℃ in air atmosphere for 1000h. The oxidation rate of the steel was 0.04g / m 2 ·h, reaching the standard of complete antioxidant performance, with good antioxidant performance.
[0172] Comparative Example 11
[0173] This comparative example provides a non-magnetic steel having the same composition as that of Example 3.
[0174] The steel smelting process is exactly the same as that in Example 3. The ingot is heated in a three-stage heating furnace. The heating furnace is heated by natural gas, and the volume proportion of atmospheric oxygen is controlled to be less than 2%. The initial temperature is controlled at 1150°C, the middle temperature is controlled at 1250°C, the soaking temperature is controlled at 1150°C, the billet temperature out of the heating furnace is controlled at 1100°C, and the total heating time is 90min. The opening temperature is controlled at 1050°C, and the final temperature is controlled at 730°C. Water dephosphorization is performed once during the rolling process. The final cooling temperature is controlled at 500°C, followed by air cooling.
[0175] After testing, the steel has an austenite structure and a magnetic permeability of 1.002 at a magnetic field strength of 200 oersteds. The yield strength at room temperature is 554MPa and the tensile strength is 762MPa. The initial yield strength at 600-800°C is 481MPa and the tensile strength is 543MPa. After 5 days of high-temperature creep, the yield strength is increased to 510MPa and the tensile strength is 601MPa. Compared with Example 3, the final cooling temperature is controlled to 500°C, which is lower than the set temperature of this application. The VC precipitation time is short, the precipitation amount is small, the room temperature mechanical properties are low, and a large amount of precipitation occurs during the subsequent high-temperature service process, which is helpful for the high-temperature mechanical properties.
[0176] The steel was tested according to the national standard GB / T 13303-1991. The steel was calcined at 600℃ in air atmosphere for 1000h. The oxidation rate of the steel was 0.04g / m 2 ·h, reaching the standard of complete antioxidant performance, with good antioxidant performance.
[0177] Comparative Example 12
[0178] This comparative example provides a non-magnetic steel having the same composition as that of Example 3.
[0179] The steel smelting process is exactly the same as that in Example 3. The ingot is heated in a three-stage heating furnace. The heating furnace is heated by natural gas, and the volume proportion of atmospheric oxygen is controlled to be less than 2%. The initial temperature is controlled at 1150°C, the middle temperature is controlled at 1250°C, the soaking temperature is controlled at 1150°C, the billet temperature out of the heating furnace is controlled at 1100°C, and the total heating time is 90min. The opening temperature is controlled at 1050°C, and the final temperature is controlled at 800°C. Water dephosphorization is performed once during the rolling process. The final cooling temperature is controlled at 650°C, followed by air cooling.
[0180] After testing, the steel is austenitic, and the magnetic permeability is 1.002 at 200 oersted magnetic field strength. The yield strength is 551MPa at room temperature and the tensile strength is 746MPa. The initial yield strength is 501MPa and the tensile strength is 583MPa at 600-800°C. After 5 days of high-temperature creep, the yield strength is increased to 521MPa and the tensile strength is 592MPa. Compared with Example 3, the final staking temperature is controlled at 800°C, which will make the austenitic structure coarse and the structure uneven, affecting the performance of the steel.
[0181] The steel was tested according to the national standard GB / T 13303-1991. The steel was calcined at 600℃ in air atmosphere for 1000h. The oxidation rate of the steel was 0.04g / m 2 ·h, reaching the standard of complete antioxidant performance, with good antioxidant performance.
[0182] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A heat-resistant high manganese non-magnetic steel, characterized in that: Taking the total mass as 100%, it is composed of the following ingredients: C0.17-0.20%, Si0.9-1.2%, Mn21.5-24.5%, Al2.0-2.6%, Cr3.5-4.2%, V0.05-0.1%, Nb0.02-0.1%, P≤0.005%, S≤0.006%, the balance is Fe and unavoidable impurities; the content ratio of Al and Cr is controlled to be 1:(1.8-2.1); The heat-resistant high manganese non-magnetic steel has a yield strength greater than 500MPa and a tensile strength greater than 700MPa at room temperature; a yield strength greater than 400MPa and a tensile strength greater than 550MPa at 600-800°C; and a magnetic permeability less than 1.005 at a magnetic field strength of 200 Oersteds. The preparation method of the heat-resistant high manganese non-magnetic steel comprises: The raw materials are sequentially subjected to electric furnace / converter smelting, AOD furnace refining, LF refining, continuous casting, heat treatment, rolling and cooling to obtain the heat-resistant high manganese non-magnetic steel; After the electric furnace / converter smelting is completed, Al particles are used for deep deoxidation; the continuous casting billet is flame cut, and the billet defects are removed by surface grinding; and then sent to a three-stage heating furnace for the heat treatment; the initial stage temperature of the heat treatment is 1100-1150°C, the middle stage temperature is 1200-1250°C, the soaking stage temperature is 1100-1150°C, the temperature out of the heating furnace is 1050-1100°C, and the total heating time does not exceed 90 minutes; The starting rolling temperature is 980-1050°C, and the final rolling temperature is 700-730°C; The cooling comprises: first cooling to 580-650° C. by air cooling plus water cooling, and then cooling to room temperature by air cooling.
2. The heat-resistant high manganese non-magnetic steel according to claim 1, characterized in that: When the surface grinding is performed, 3 mm is ground off the upper surface and 1 mm is ground off the lower surface.
3. The heat-resistant high manganese non-magnetic steel according to claim 1, characterized in that: The three-stage heating furnace is heated by natural gas.
4. The heat-resistant high manganese non-magnetic steel according to claim 3, characterized in that: The volume proportion of oxygen in the atmosphere of the three-stage heating furnace is controlled within 2%.
5. The heat-resistant high manganese non-magnetic steel according to claim 1, characterized in that: During the rolling process, water dephosphorization is performed at least once.
6. The heat-resistant high manganese non-magnetic steel according to claim 1, characterized in that: The heat-resistant high manganese non-magnetic steel is an austenite structure.
Citation Information
Patent Citations
Novel electromagnetic stirring non-magnetic steel
CN104694843A
Forging method of fe‑mn austenitic non-magnetic steel
CN106048208B
Novel high-strength high-corrosion-resistance non-magnetic stainless steel and manufacturing method thereof
CN106756526A
Non-magnetic steel and preparing method thereof
CN109811274A
Corrosion-resistant non-magnetic steel and its preparation method
CN110578099B